2001
DOI: 10.1177/135910530100600404
|View full text |Cite
|
Sign up to set email alerts
|

Lay Attitudes toward Genetic Testing for Susceptibility to Inherited Diseases

Abstract: One of the most important issues facing legal and medical policy makers in the coming years will be whether to employ populationbased testing for genetic markers of inherited diseases. Two hundred and twenty-six randomly selected individuals from Easton, Pennsylvania completed a mail questionnaire that was designed to assess the general public's attitudes toward many of the personal and societal issues surrounding genetic testing for disease susceptibility. Respondents were generally optimistic about the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 54 publications
3
45
0
Order By: Relevance
“…Several survey-based studies have found that anxieties about genetic testing vary more in cases where the test is diagnostic but the disease is untreatable and additionally have higher anxiety in cases of cancer when the test is not diagnostic than in cases where treatment is known and effective (Shaw and Bassi 2001;Gaff et al 2005). Lastly, in order for a FH screening program to be effective, individuals need to be willing to make behavioral changes to treat FH.…”
Section: Discussionmentioning
confidence: 99%
“…Several survey-based studies have found that anxieties about genetic testing vary more in cases where the test is diagnostic but the disease is untreatable and additionally have higher anxiety in cases of cancer when the test is not diagnostic than in cases where treatment is known and effective (Shaw and Bassi 2001;Gaff et al 2005). Lastly, in order for a FH screening program to be effective, individuals need to be willing to make behavioral changes to treat FH.…”
Section: Discussionmentioning
confidence: 99%
“…20 -22 Another study showed that the lay public was generally optimistic about the potential benefits of genetic susceptibility testing. 23 It is important to note, however, that interest in predictive testing often does not translate into actual test uptake, as was seen in the case of Huntington disease. 24 The nature of the information presented as part of the risk assessment, as well as how the information was communicated by the genetic counselors, may have also contributed to participants' favorable perceptions of genetic information.…”
Section: Impact Of Genetic Testing On Ad Risk Perceptionmentioning
confidence: 99%
“…In a study by Shaw and Bassi [7], healthy adults expressed greater intention to undergo genetic screening for curable diseases, than for those with no cure, which is consistent with people's desire to assert control in their lives. Similarly, Roberts [8] found that first-degree relatives of people with Alzheimer's were more likely to report test-taking intention when presented with hypothetical scenarios where treatment to prevent or delay disease onset was available.…”
Section: Introductionmentioning
confidence: 82%
“…Four fictitious diagnoses (Renibus disease, Iecur disease, Mesencephalon disorder and Prosencephalon disorder) were created for the scenarios to control for participants' prior knowledge and experiences of diseases, as potential confounding variables. In the treatment available scenario participants received a positive test result for the invented Renibus or Iecur diseases and in the no treatment available scenario a predisposition to the fictitious Mesencephalon or Prosencephalon disorders, adapted from Roberts [8] and Shaw, Bassi [7] (see Table 1). Penetrance was operationalised using absolute risk values.…”
Section: Hypothetical Disease Scenariosmentioning
confidence: 99%